The implementation checklist: A pragmatic instrument for accelerating research‐to‐implementation cycles - Stephanie Prausnitz; Andrea Altschuler; Lisa J. Herrinton; Andrew L. Avins; Douglas A. Corley (Wiley, 2023)
Abstract Introduction Learning health systems require rapid‐cycle research and nimble implementation processes to maximize innovation across disparate specialties and operations. Existing detailed research‐to‐implementation frameworks require extensive time commitments and can be overwhelming for physician‐researchers with clinical and operational responsibilities, inhibiting their widespread adoption. The creation of a short, pragmatic checklist to inform implementation processes may substantially improve uptake and implementation efficiency across a variety of health systems. Methods We conducted a systematic review of existing implementation frameworks to identify core concepts. Utilizing comprehensive stakeholder engagement with 25 operational leaders, embedded physician‐researchers, and delivery scientists, concepts were iteratively integrated to create and implement a final concise instrument. Results A systematic review identified 894 publications describing implementation frameworks, which included 15 systematic reviews. Among these, domains were extracted from three commonly utilized instruments: the Quality Implementation Framework (QIF), the Consolidated Framework for Implementation Research (CFIR), and the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE‐AIM) framework. Iterative testing and stakeholder engagement revision of a four‐page draft implementation document with five domains resulted in a concise, one‐page implementation planning instrument to be used at project outset and periodically throughout project implementation planning. The instrument addresses end‐user feasibility concerns while retaining the main goals of more complex tools. This instrument was then systematically integrated into projects within the Kaiser Permanente Northern California Delivery Science and Applied Research program to address stakeholder engagement, efficiency, project planning, and operational implementation of study results. Conclusion A streamlined one‐page implementation planning instrument, incorporating core concepts of existing frameworks, provides a pragmatic, robust framework for evidence‐based healthcare innovation cycles that is being broadly implemented within a learning health system. These streamlined processes could inform other settings needing a best practice rapid‐cycle research‐to‐implementation tool for large numbers of diverse projects.